Mechanisms for exporting large-sized cargoes from the endoplasmic reticulum - Saito, Kota (Cell Mol Life Sci, 2015)
Cargo proteins exported from the endoplasmic reticulum to the Golgi apparatus are typically transported in coat protein complex II (COPII)-coated vesicles of 60–90 nm diameter. Several cargo molecules including collagens and chylomicrons form structures that are too large to be accommodated by these vesicles, but their secretion still requires COPII proteins. Here, we first review recent progress on large cargo secretions derived especially from animal models and human diseases, which indicate the importance of COPII proteins. We then discuss the recent isolation of specialized factors that modulate the process of COPII-dependent cargo formation to facilitate the exit of large-sized cargoes from the endoplasmic reticulum. Based on these findings, we propose a model that describes the importance of the GTPase cycle for secretion of oversized cargoes. Next, we summarize reports that describe the structures of COPII proteins and how these results provide insight into the mechanism of assembly of the large cargo carriers. Finally, we discuss what issues remain to be solved in the future.